CONTROLLING AS A CORPORATE GOVERNANCE TOOL - T. Rogulenko (Вестник университета)
The issues of the formation of controlling as a tool for corporate governance, in-formation and analytical support of management objectives were studied. The principles and foundations of its formation for the tactical and strategic goals of business manage-ment has been determined. According to the results of the research it is concluded that con-trolling is one of the modern algorithmic and automated tools of the corporate governance system of the economic development strategy in a highly competitive environment and un-predictability of the behavior of economic entities in the market of goods, works, services, currency, securities and etc., which integrates with other management systems in the mode of their parallel automation.